Purification & characterization of Glycans of Uromodulin from anemia pregnant women - Lim, Lai Suan (Universiti Malaysia Sabah, 2008)
Tamm-Horsfall protein (TIIP) and Uromodulin (UM) are glycoproteins produced and excreted from kidney to urine. The molecular size of THP and UM is about 80k:Da. The carbohydrate moiety ofTHP and UM is 30% of the total molecular weight. TlIP and UM contained both O-glycans and N-glycans. THP and UM have same amino acid sequence but different in glycosylation part. UM is representing THP in pregnancy. The main role of THP and UM is immunosuppressive effect on T-cell. UM have 13 fold more effective in immunosuppressive effect than TlIP due to the glycosylation different. The glycosylation of UM in pregnant women associated to anemia is studied in this paper. UM of normal pregnant and THP of female anemia and male anemia were act as a control. In this study, the UM was isolated from anemia and normal pregnant women urine in second trimester and third trimester of pregnancy period. The percentage of protein contain of each samples was measured by Bradford method. It found that the percentage of protein content of fifth month pregnancy is highest in anemia pregnant, while third month pregnancy contamt the highest amount of protein in normal pregnant. The averages of protein content in non-